Preparation of Symmetrical and Nonsymmetrical Fluorene Sulfonamide Scaffolds - Jones, D. Heulyn; Tellam, James P.; Bresciani, Stefano; Wojno-Picon, Justyna; Cooper, Anthony W. J.; Tomkinson, Nicholas C. O. (Synlett, 2017)
Methods for the preparation of symmetrical and nonsymmetrical 2,7-disubstituted 9H-fluorene derivatives are described.
Keywords: fluorene; sulfonamide; microwave-assisted synthesis